Cork oak (Quercus suber L.) site rating - Gonçalves, Ana Cristina (2004)
Alentejo cork oak stands are crucial in terms of cork production and sustainability of agrosilvopastoral systems, therefore the development of a tool that allows site zoning, according to cork oak establishment and growth potentials is worthwhile. The site potential and consequently tree development are mainly governed by soil characteristics such as depth, permeability, chemistry, internal drainage, runoff and climate characteristics such as precipitation and temperature. A cork oak site-rating index, as a function of the above characteristics, was implemented allowing the definition and grading of areas for growth and development. The information was integrated in a GIS environment, using geoprocessing and spatial analysis resulting in the production interpretative maps.